The Sum of Fears in Cancer Patients Inside the Context of the COVID-19 - Bandinelli, Lucas; Ornell, Felipe; von Diemen, Lisia; Kessler, Felix Henrique Paim (Frontiers in Psychiatry, 2021)
The pandemic resulting from COVID-19 has led to the collapse of the health system in dozens of countries. Parallel to clinical risk, the appearance or intensification of psychiatric symptoms has also been documented. The identification of groups at risk is essential for the establishment of preventive and therapeutic strategies. Cancer patients appear to be especially vulnerable both from a clinical and psychiatric perspective. Problems related to contamination and the cancer treatments themselves are intertwined, causing a sum of patients' fears to arise, which can cause mental effects. This study aims to review and investigate the impact of COVID-19 on the mental health of cancer patients and indicate possible support strategies.